Comparative Analysis of Transparency in Conventional and Blockchain Zakat Management - Hasan, Hurriah Ali (Universitas Muhammadiyah Makassar, 2025)
Zakat management has an important role in realizing a just and sustainable Islamic economic system. However, the practice of conventional zakat management still faces various problems, especially related to transparency and trust of muzakki. Periodic financial statements, manual recording that is prone to errors, and the absence of an independent verification mechanism, can raise doubts among muzakki about the accountability of zakat institutions. Meanwhile, the development of blockchain technology offers alternative solutions through decentralized, immutable, transparent recording mechanisms, and automation features through smart contracts. This study aims to analyze the difference in transparency and the level of trust between conventional zakat management and zakat management using a blockchain-based system. The research method uses a qualitative-descriptive approach through literature review, comparative analysis, and conceptual analysis. The results of the study show that blockchain is able to provide real-time transparency, permanent trail audits, and open verification that significantly increases muzakki's trust. Thus, the integration of blockchain in zakat management has the potential to strengthen institutional accountability, increase public legitimacy, and create more modern and reliable zakat governance.